Leveraging an implementation–research partnership to improve effectiveness of nutrition-sensitive programs at the World Food Programme - Olney, Deanna K.; Marshall, Quinn; Honton, Geraldine; Ogden, Kathryn; Hambayi, Mutinta; Piccini, Sarah; Go, Ara; Gelli, Aulo; Bliznashka, Lilia (SAGE Publications, 2020)
Nutrition-sensitive programs can accelerate progress in addressing malnutrition. However, evidence gaps exist related to their effectiveness and how to optimize program design and implementation.We present the process the International Food Policy Research Institute and the World Food Programme (WFP) used to develop nutrition-sensitive program guidance and plans for improving program effectiveness and contributing to the evidence base through rigorous evaluations.A 5-step process, using principles of design thinking (a systematic, iterative analytical approach to problem solving), was used to develop, test, and refine WFP’s nutrition-sensitive guidance. The guidance focuses on improving nutrition outcomes for nutritionally vulnerable groups across the life cycle: women and children in the first 1000 days, preschoolers, schoolchildren, and adolescents.Through iterative consultations, we created WFP’s nutrition-sensitive guidance that includes harmonized theories of change across WFP’s programs; 7 opportunities to enhance the programs’ nutrition-sensitivity; and mapping of these opportunities to WFP programs and key evidence gaps. This guidance has been rolled out to WFP’s offices worldwide to support improved nutrition outcomes. Finally, several evaluation designs have been proposed to fill identified evidence gaps.By leveraging our implementation–research partnership, we expect that WFP’s programs will be more effective and cost effective for improving nutrition. This can be assessed through coupling newly designed nutrition-sensitive programs with rigorous evaluations. Evaluation results will be used to refine WFP’s nutrition-sensitive guidance and improve their programs globally. This guidance, and creation process, could be useful for others interested in designing nutrition-sensitive programs and increasing program effectiveness for nutrition.